The regulation of long non-coding RNA 00958 (LINC00958) for oral squamous cell carcinoma (OSCC) cells death through absent in melanoma 2 (AIM2) depending on microRNA-4306 and Sirtuin1 (SIRT1) in vitro. Issue 1 (1st January 2021) - Jiang, Lei; Ge, Wenyu; Cui, Yifei; Wang, Xiaofeng
ABSTRACT: Long non-coding RNAs (lncRNAs) have been proposed as potential targets in OSCC gene therapy. Thus, the study aims to analyze how they exert functions in OSCC. LINC00958, AIM2, Gasdermin D (GSDMD) and tumor protein p53 (TP53) expression levels are analyzed by Quantitative Real-time PCR (qPCR) or Western blotting (WB) in OSCC cells lines. The roles of LINC00958 in cell proliferation, cell death, and GSDMD expression respectively were analyzed by Cell Counting Kit-8 (CCK8) assay, flow cytometry and Immunofluorescence (IF) assay. In addition, expressions of pyroptosis- and autophagy-related proteins are evaluated by WB detection. The targeted binding of LINC00958 and miR-4306 or AIM2 mRNA is predicted by bioinformatics analysis and detected by biodual luciferase system. RIP and qPCR assays analyze whether LINC00958 interacts with SIRT1. We found that LINC00958 showed upregulation in OSCC cells compared to normal oral epithelial cells. LINC00958 silencing significantly suppressed OSCC cell proliferation, induced cell death and reduced autophagy. LINC00958 regulated the levels of miR-4306 which binds to the 3ʹUTR of AIM2, and interacts with and modulates SIRT1 protein expression. LINC00958 regulated GSDMD and AIM2 levels, as well as p53 and SIRT1 levels. SIRT1 overexpression markedly reversed aforementioned effects of LINC00958. LINC00958 not only downregulated miR-4306 levels to activate the pyroptosis pathway mediated by AIM2 and promoted cancer cell survival but also induced a decrease in SIRT protein expression to further reduce p53 levels. Graphical abstract: uf0001